2018
DOI: 10.1039/c8ra03623c
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the reducibility and catalytic activity of CuO nanoparticles for low temperature CO oxidation

Abstract: . Furthermore, the tailored catalysts exhibited excellent long-term stability for CO oxidation for up to 48 h on stream. These readily-reducible CuO nanoparticles could serve as efficient, inexpensive and durable catalysts for CO oxidation at low temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 64 publications
(71 reference statements)
2
36
0
1
Order By: Relevance
“…Copper oxide (CuO) has been considered to be one of the best semiconductor metal oxides as a result of its important chemical and physical properties such as large surface area, excellent solar light absorbance, and a narrow band gap (1.2 eV) [ 8 , 9 , 10 , 11 ]. CuO materials have a monoclinic structure and numerous attractive aspects, such as high stability, super thermal conductivity, photovoltaic properties, and antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Copper oxide (CuO) has been considered to be one of the best semiconductor metal oxides as a result of its important chemical and physical properties such as large surface area, excellent solar light absorbance, and a narrow band gap (1.2 eV) [ 8 , 9 , 10 , 11 ]. CuO materials have a monoclinic structure and numerous attractive aspects, such as high stability, super thermal conductivity, photovoltaic properties, and antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they have antimicrobial properties against a wide range of pathogenic microorganisms [ 9 ], but their use in medical applications has been questioned due to their high toxicity [ 10 , 11 ]. One of the main applications of nanoscale structures of copper and its oxides is heterogeneous catalysis systems, and these NSs perform more efficiently compared to bulk analogs [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the Cu nanoparticles used experimentally have an average diameter of B30 nm for catalytic CO oxidation, 19 while they are in the range of 15-35 nm for copper oxide catalysts. 24,25 A smaller copper oxide catalyst with a particle size of 3.6 nm was obtained by specific preparation methods, 26 and it displays an enhanced catalytic activity. Moreover, previous studies have revealed that the CO oxidation conversion rate is considerably affected by the crystal size of the catalyst where it generally increases up to an optimal crystal size, after which the conversion rate decreases again.…”
Section: Introductionmentioning
confidence: 99%